PERBANDINGAN YURIDIS HAK VETO PRESIDEN TERHADAP RANCANGAN UNDANG UNDANG ANTARA INDONESIA DENGAN AMERIKA SERIKAT - Nababan, Eprin Erikson; Haryono, Dodi; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Article 5 Paragraph (1) explains that the President as one of theexecutives has the right to submit bills to the DPR as a legislative institution.Article 20 also regulates the formation of the bill. The joint agreement on thelegislative function in the Indonesian presidential system of government dividesauthority. The refusal made by one party opens the possibility of tension inrelations between the DPR and the President. Second, to find out the similaritiesand differences in presidential veto power on draft laws in Indonesia and theUnited States. Third, to find out the advantages and disadvantages of thepresident's veto power over draft laws in Indonesia and the United States.The research method in this thesis uses a type of normative juridicalresearch, which is research focused on examining the application of rules ornorms in positive law. The nature of this thesis research is descriptive researchthat describes systematically, the facts and characteristics of the object understudy precisely. The data sources used are primary, secondary and tertiary datasources, The data collection method used in this study is the first literature study,is a technique to obtain secondary data through documents related to theproblem, objectives and benefits of research, then after the data is collected thenanalyzed to draw conclusions.Based on the results of research, in Indonesia veto power is the right todeclare rejection of a draft law or to the material of a bill in the planning,drafting, and discussion stages. While in America the veto power is at the stage ofdetermination (approving) The explanation above has explained that in Indonesiathe constitution only gives